Performance Effects of Global Account Coordination Mechanisms: An Integrative Study of Boundary Conditions. Issue 2 (June 2016) - Shi, Linda Hui; Gao, Tao (Tony)
Although many multinational companies have instituted global account management (GAM) programs to coordinate selling activities to better serve and retain their key global customers, evidence of the effectiveness of their GAM coordination efforts is elusive. Viewing GAM coordination as an organizational design issue in managing vertical procurement relationships, the authors draw on global marketing strategy, organizational design, and relationship marketing theories to study how the performances of GAM coordination mechanisms vary with a host of strategic, relational, and environmental conditions. The conceptual model is tested using data collected from a cross-national sample of more than 200 global account managers. The results show that although GAM relational coordination and GAM operational coordination both have positive effects on GAM performance, they do not perform uniformly well under various boundary conditions. In other words, the performance of a GAM coordination mechanism depends on its fit with the operating context.